2021
DOI: 10.9756/int-jecse/v13i2.211099
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination, Stress and Academic Engagement in Medicine Students

Abstract: In the study titled Procrastination, stress in academic engagement in Medicine students of a private university, the objective is to establish the relationship between procrastination and stress in the academic engagement of Medicine students of a private university according to sex and age. The approach used was quantitative, descriptive method, and basic. The population was 1904 Medicine students of the private university, the sample was 320 Medicine students, a stratified probability sampling method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is due to declining social support, unemployment, lack of access to healthcare, financial decline [65], [78], and the uncertainty of the pandemic's end [68], [73]. The impact of the pandemic on the decline in student mental health is due to economic pressure, fear of exposure to the virus [70], decreased attention from parents due to inhibition of interaction and communication [52], and decline in physiological health due to lack of quality sleep [47]. From a sample of 209 students, 68% female, 82% freshmen, 50% Asian, 32% Hispanic, 13% white, and 5% other from a public university in Southern California, USA, it was found that declining mental health included concentration difficulties, academic performance concerns and increased task load [32].…”
Section: Student Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to declining social support, unemployment, lack of access to healthcare, financial decline [65], [78], and the uncertainty of the pandemic's end [68], [73]. The impact of the pandemic on the decline in student mental health is due to economic pressure, fear of exposure to the virus [70], decreased attention from parents due to inhibition of interaction and communication [52], and decline in physiological health due to lack of quality sleep [47]. From a sample of 209 students, 68% female, 82% freshmen, 50% Asian, 32% Hispanic, 13% white, and 5% other from a public university in Southern California, USA, it was found that declining mental health included concentration difficulties, academic performance concerns and increased task load [32].…”
Section: Student Mental Healthmentioning
confidence: 99%
“…Education in universities was disrupted during the pandemic because students experienced pathological expressions ranging from anxiety, depression, stress, and feelings of sadness [42], [38]. The impact of student academic stress occurs due to increased academic procrastination [52], fear of virus transmission and up to academic tasks [37]; the pressure is also exacerbated by symptoms of depression and loneliness [40]. Based on research in the United States, academic stress is alleviated through real-time stress mitigation [67], online therapy, face-to-face clinical therapy, resilience, mediation, and stress mindset intervention [55], [58], [72].…”
Section: Impact Of Academic Stress On Studentsmentioning
confidence: 99%